The relationship between learning strategies and learning styles in the development of english students' oral proficiency in reading and conversation I, semester II, 2012 - Zarceño Interiano, Julia Marleni,
This paper reports on the findings of a study conducted to investigate the language Learning Strategies used by students of the Foreign Languages Department of the University of El Salvador and their Learning Style with Oral Proficiency Development. The study found that there was a significant relationship between the correct use of Learning Strategies according to students’ Learning Styles and English Oral Proficiency. It was found that the more a student used a variety of language Learning Strategies that match their learning styles, the more proficient a student became in language learning, and the use of some specific strategies was positively correlated to improvement of sub-language skills such as oral communication.